Parental management of feeding problems in young children-a population-based study. (September 2020) - Sdravou, Katerina; Andreoulakis, Elias; Printza, Athanasia; Sotiriadou, Fotini; Evangeliou, Athanasios; Fotoulaki, Maria
Abstract: Objectives: To investigate the practices that parents use to manage feeding problems in healthy children and in children with gastrointestinal diseases. Secondly, for each of these two groups we examined the association of select child and parent variables with parental feeding practices. Methods: This is a cross-sectional case-control study. The sample consisted of 901 children (765 healthy children of typical development and 136 children with gastrointestinal diseases), aged one to seven years. The feeding problem management practices were investigated through 23 closed-ended questions. The anthropometric and demographic data of children and the demographic data of parents were collected by administering structured set of questions to parents. Results: The prevalence of parent-reported feeding problems was 30.6% for healthy children and 45.7% for children with gastrointestinal diseases. The most common practices adopted by parents of healthy children were highlighting the benefits of food (80.5%), correlating food with pleasure (71.6%) and praising (59.1%), whereas almost half of the parents were found not to accept that their children may not be hungry and insisted on trying to feed them. Statistically significant differences were noted in many parental practices between the two groups. Parents of children with gastrointestinal diseases were generally more involved in the feeding process. Verbal praising (69.1%), correlation with pleasure (79.4%), promotion of benefits (77.2%) as well as assistance during feeding (63.2%) were the most common parental practices in the gastrointestinal group. Age, birth order, being the only child and weight status were child variables that differentiated parental behavior. Parental characteristics that affected feeding practises were age, education and work status. Conclusions: A high prevalence of feeding problems was reported by parents of both healthy children and children with gastrointestinal diseases. Beside the presence of a disease, specific child and parent variables are significantly related to parental behavior when managing feeding problems. Highlights: High prevalence of feeding problems in young children. Specific child and parent characteristics influence parental feeding practices. More than half of the parents distrust the child's own appetite during feeding. Parents of children with digestive disorders are more actively involved in feeding. Parents emphasize the positive aspects of feeding when managing feeding problems.